Optical, structural and morphological properties of CdS-CdCO_3 films. - Chávez Portillo, M.; Sosa Sánchez, A.; Juárez Díaz, G.; A, L.; Cruz Cruz, S.; Gutierrez Pérez, R.; Hernández Téllez, G.; Portillo Moreno, O. (Revista Mexicana de Física, 2015)
CdS-CdCO_3 thin films were grown by chemical bath deposition. Different constant deposition temperatures were employed in the range of 20-80^°C. From X-ray Diffraction (XRD) results can be observed that intensity of CdS peak is abruptly reduced when deposition temperature is decreased. By SEM images the formation and change in shape and size of crystallites can be observed as temperature is decreased. The forbidden energy band gap was 2.4-4.1 eV, determined from optical absorption. The formation of products was further confirmed with FTIR studies.